A Systematic Review and Meta-Analysis of Male Infertility and the Subsequent Risk of Cancer - Behboudi-Gandevani, Samira; Bidhendi-Yarandi, Razieh; Panahi, Mohammad Hossein; Vaismoradi, Mojtaba (Frontiers in Oncology, 2021)
Objectives: The primary objective of this systemic review and meta-analysis was to investigate the risk of developing composite outcome of all cancers, regardless of the type of cancer among men with infertility diagnosis compared to fertile counterparts. The secondary objective was to compare the pooled risk of developing individual specific cancers between two groups. Methods: A systematic literature search was performed. Studies assessed cancer events in males with an infertility diagnosis compared to controls without infertility. The outcomes of interest were a composite outcome of cancers including all known cancer types, and also specific individual cancers. The pooled odds ratio of cancers was calculated using the DerSimonian and Laird, and inverse variance methods. Studies’ quality and risk of bias were assessed using structured standard tools. Results: We included eight cohort studies involving 168,327 men with the diagnosis of infertility and 2,252,806 men without it. The number of composite outcome of cancers as well as individual cancers including prostate, testicular and melanoma were 1551, 324, 183 and 121 in the infertile men and 12164, 3875, 849, and 450 in the fertile men, respectively. The pooled OR of the composite outcome of cancers, regardless of the type of cancer, in men with infertility was 1.4 folds higher than those without infertility (pooled OR = 1.43, 95% confidence interval [CI]: 1.25-1.64). Meta-analysis of individual cancers including prostate, testicular and melanoma between two groups was carried out. The pooled ORs of testicular and prostate cancers in men with the diagnosis of infertility were significantly higher than controls without infertility (pooled OR = 1.91, 95% CI: 1.52-2.42 and pooled OR = 1.48, 95% CI: 1.05-2.08, respectively). Additionally, the pooled OR of melanoma in men with infertility was 1.3 folds higher than those without infertility (pooled OR = 1.31, 95% CI: 1.06-1.62). Conclusion: A greater risk of cancers in men with male infertility was found suggesting that the history of male infertility might be an important risk factor for developing cancers in later life. Further well-designed long-term population-based prospective studies, considering all known cancers and their accompanying risk factors should be conducted to support our findings.